Prognostic impact of intra tumoral HPV-16 viral load in oropharyngeal squamous cell carcinomas - Villarmé, Agathe; Ebran, Nathalie; Pace-Loscos, Tanguy; Schiappa, Renaud; Mignot, Audrey; Bozec, Alexandre; Sudaka-Bahadoran, Anne; Saada-Bouzid, Esma; Culié, Dorian (Oral oncology, 2024)
•HPV-related oropharyngeal squamous cell carcinomas have a more favorable prognosis than those linked to tobacco.•Oropharyngeal cancers both linked to tobacco and HPV have an intermediate prognosis.•In a series of 192 patients, we highlight an independent prognostic role of HPV viral load.•Subject to confirmation on independent prospective cohorts, HPV viral load may help to refine the prognosis of oropharyngeal cancers. The incidence of HPV-induced oropharyngeal squamous cell carcinoma (OSCC) is constantly increasing. Although HPV-related OSCC carry a better prognosis, the majority of patients with an HPV-positive OSCC have other prognostic factors such as tobacco smoking, making therapeutic de-escalating approaches less precise. In this context, our study aims to evaluate the prognostic impact of intra-tumoral HPV-16 viral load (VL) in OSCC. We conducted a retrospective analysis of p16-positive OSCC samples from patients treated between 2012 and 2019. Viral load (VL) was determined using digital droplet Polymerase Chain Reaction (ddPCR) and described according to 3 subgroups: low (<0.9 copies/cell), medium (0.9–85 copies/cell), and high (>85 copies/cell). We assessed the correlation between VL and recurrence-free survival (RFS), specific survival (SS), and overall survival (OS) using the Kaplan-Meier method. In total, 192 patients were included; 148 (77 %) were male. The mean age was 65. HPV-16 was detected in 189/192 samples (98 %). T3-4-stage (p = 0.002), metastasis (p = 0.007), and tobacco consumption (p = 0.01) predicted lower OS. High VL was associated with higher RFS (HR = 0.2, p = 0.01), SS (HR = 0.32, p = 0.02), and OS (HR = 0.39, p = 0.03). After adjusting for tobacco consumption and tumor stage, high VL remained associated with higher RFS (HR = 0.1, 95 %CI [0.04–0.7], p = 0.01) and SS (HR = 0.20, 95 %CI [0.05–0.75], p = 0.01). In our study, high intra-tumoral HPV VL was independently associated with survival. Subject to further validation in independent and prospective cohorts, our findings suggest that HPV VL could help to refine the prognosis of HPV positive OSCC patients.